Assessment-for-Learning-Based Student Activity Sheets on Reaction Rate to Improve Students’ Science Process Skills - Saifulloh, Moh. Threewahyu; Agustini, Rudiana (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Science process skills remain underdeveloped in many chemistry classrooms due to limited use of structured, feedback-oriented learning materials. This study aimed to develop Student Activity Sheets (Lembar Aktivitas Murid/LAM) based on Assessment for Learning (AfL) principles to improve students' science process skills in reaction rate material. This study used a Research and Development design based on the 4D model, limited to the Define, Design, and Develop stages. The product was validated by two chemistry education lecturers and one chemistry teacher. Practicality was evaluated through student response questionnaires and activity observation sheets, while effectiveness was examined using a one-group pretest-posttest design involving 34 grade XI students at SMAN 1 Menganti. The results showed that the LAM was valid, with a mode score of 4 across content, construct, and language validity aspects. The product was also very practical, with student response and observation scores of 98.53% and 89.25%, respectively. The Wilcoxon signed-rank test confirmed a statistically significant improvement between pretest and posttest scores (Z = −5.093, p < .001), with a large effect size (r = 0.87). N-gain analysis revealed an overall mean gain of 0.73 (high category), with four indicators in the high category — collecting data (0.83), identifying variables (0.81), analyzing data (0.78), and formulating problems (0.74) — and two in the medium category — drawing conclusions (0.63) and constructing hypotheses (0.61). These findings indicate that the AfL-based LAM is feasible and effectively supports the development of students' science process skills in reaction rate learning.